Metacognitives And Morals: The Qur’an As A Guide - et. al., Aminah Binti Mat Yusoff, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Education is one of the main mediums that support towards generating a paradigm shift of each individual, excelling in many aspects that include spiritual, emotional and physical aspects. It is undeniable that the Education sector is growing rapidly in increasing access, equity and quality in Education today. Cooperation from all parties will provide a bright opportunity to develop the generation that will lead the country in the future. Efforts to restore the morals of children and guide them to the right path based on the guidance from the Qur'an should start from the beginning of birth until they grow into adulthood. Therefore, this study was conducted to find out what are the components, strategies and processes needed to improve metacognitive skills contained in the Quran and Hadith of the Prophet SAW in controlling every thought and action and ultimately affect the formation of morals. human.